Biochar stimulates tomato roots to recruit a bacterial assemblage contributing to disease resistance against Fusarium wilt. Issue 3 (23rd June 2022) - Jin, Xue; Bai, Yang; Khashi u Rahman, Muhammad; Kang, Xiaojun; Pan, Kai; Wu, Fengzhi; Pommier, Thomas; Zhou, Xingang; Wei, Zhong
Abstract: Biochar amendment is acknowledged to favor plant resistance against soil‐borne diseases. Although plant‐beneficial bacteria enrichment in the rhizosphere is often proposed to be associated with this protection, the mechanism behind this stimulating effect remains unelucidated. Here, we tested whether biochar promotes plants to recruit beneficial bacteria to the rhizosphere, and thus develop a disease‐suppressive rhizosphere microbiome. In a pot experiment, biochar amendment decreased tomato Fusarium wilt disease severity. Using a transplanting rhizosphere microbiome experiment, we showed that biochar enhanced the suppressiveness of tomato rhizosphere microbiome against Fusarium wilt disease. High‐throughput sequencing of 16S ribosomal RNA gene and in vitro cultures further indicated that the recruited suppressive rhizosphere microbiome was associated with the increase of plant‐beneficial bacteria, such as Pseudomonas sp. This amendment also enhanced the in vitro chemoattraction and biofilm promotion activity of tomato root exudates. Collectively, our results demonstrate that biochar amendment induces tomato seedlings to efficiently recruit a disease‐suppressive rhizosphere microbiome against Fusarium wilt. Abstract : Biochar enhances the disease suppressiveness of tomato rhizosphere microbiome. Biochar stimulates tomato to actively recruit plant‐beneficial bacterial taxa. The ability of tomato root exudates to recruit beneficial bacteria is enhanced by biochar. Highlights: Biochar enhances the disease suppressiveness of tomato rhizosphere microbiome. Biochar stimulates tomato to actively recruit plant‐beneficial bacterial taxa. The ability of tomato root exudates to recruit beneficial bacteria is enhanced by biochar.